Comparison of doxorubicin–cyclophosphamide with doxorubicin–dacarbazine for the adjuvant treatment of canine hemangiosarcoma. (26th January 2015) - Finotello, R.; Stefanello, D.; Zini, E.; Marconato, L.
Abstract: Canine hemangiosarcoma (HSA) is a neoplasm of vascular endothelial origin that has an aggressive biological behaviour, with less than 10% of dogs alive at 12‐months postdiagnosis. Treatment of choice consists of surgery followed by adjuvant doxorubicin‐based chemotherapy. We prospectively compared adjuvant doxorubicin and dacarbazine (ADTIC) to a traditional doxorubicin and cyclophosphamide (AC) treatment, aiming at determining safety and assessing whether this regimen prolongs survival and time to metastasis (TTM). Twenty‐seven dogs were enrolled; following staging work‐up, 18 were treated with AC and 9 with ADTIC. Median TTM and survival time were longer for dogs treated with ADTIC compared with those receiving AC (>550 versus 112 days, P = 0.021 and >550 versus 142 days, P = 0.011, respectively). Both protocols were well tolerated, without need for dose reduction or increased interval between treatments. A protocol consisting of combined doxorubicin and dacarbazine is safe in dogs with HSA and prolongs TTM and survival time.